Design Of Linear And Circular Polarized Antenna For WLAN Application - Abd Aziz., Mohamad Zoinol Abidin; Abu Bakar, Hamizan; Ahmad, Badrul Hisham; Azahari, Salleh; Ghani, Suhana; Phoo, Kho Shin; Hassan, Nornikman; Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah (Penerbit UTM Press, 2016)
In this paper, a linear and circular polarized antenna with operating frequency at 2.4 GHz for Wireless Local Area Network (WLAN) application is proposed. Firstly, a basic linear polarization antenna (Design A) was designed with rectangular slot at the rectangular patch and air gap between substrate and copper layer with distance of 10 mm. Next, in order to perform circular polarized, the antenna designed is added with optimized dual circular notch at the rectangular slot. This circular polarized antenna is designed with two different polarization types which are right-handed circular polarization (RHCP) with optimized dual circular notch at the patch (Design B) and left-handed circular polarization (LHCP) with optimized dual circular notch at the patch (Design C). The proposed antenna had been designed and simulated by using Computer Simulation Technology (CST) Microwave Studio Suite. The comparison result of simulation and measurement show that the proposed antenna can achieve axial ratio above 3 dB for linear polarized and below 3 dB for circular polarized with return loss less than -10 dB.